Pemikiran Ekonomi Abu Ubaid: Kontribusinya Terhadap Konsep Keadilan dan Distribusi dalam Ekonomi Islam - Lathifah Ananda Putri; Najwa Nabila; Ruli Pebrina br. Sitepu; Septian Dwi Cahya; Vany Fadillah Bastian; Fitri Hayati (Pusat Riset dan Inovasi Nasional, 2025)
Abu Ubaid’s economic thinking, particularly in the context of wealth distribution and social justice, provides important insights for the management of Islamic economics. Through his work Kitab al-Amwal, Abu Ubaid emphasizes the role of the state in distributing the wealth of the people fairly and the obligation of individuals to pay zakat and sedekah. His thinking that focuses On equity, transparency, and accountability in wealth management remains relevant amidst the challenges of global economic inequality. Abu Ubaid’s ideas on social justice and wealth distribution provide guidance in building a more equitable and sustainable economic system.